Enhancing cash waqf model framework for financing higher education in Malaysia : issues, challenges and prospects - Asharaf Mohd Ramli
Education has many benefits and positive impacts on people's life. In the world today, higher education plays a vital role in producing human capital that is considered an important national resource. As higher education is crucial for human resource development, the Malaysian government has allocated a substantial amount of public fund to sustain the operational expenditures of public universities and student assistance schemes. However, public funding for higher education is facing the challenge of sustainability. Studies have shown that sustainability challenge is largely due to the existing cost-sharing funding model. The literature has recommended the use of Islamic gift instrument model but has remained silent on developing such a model. Hence, this study has developed an Enhanced Cash Waqf Model Framework (ECWMF) that could be used to provide sustainable higher education financing in Malaysia. In this model, cash Waqf institution (CWI) will raise cash Waqf contributions from the public. These contributions will then be converted (istibdal) into permanent assets or invested into income-generating assets. Profits from these investments will be used by CWI as an affordable, alternative source of funds for funding public universities and student assistance schemes. The study has used mixed method (interviews and questionnaire survey). The interviews were conducted with 10 experts to validate ECWMF. The questionnaires, developed based on the Theory of Planned Behaviour, were distributed to 417 respondents, out of which 392 were usable. The interview data were analysed using thematic analysis while the data from the questionnaire survey were analysed using the Structural Equation Modelling (SEM). The study hypothesised that the behavioural intention of higher education's students to participate in the ECWMF is influenced by attitude, subjective norm, and perceived behavioural control. The results of the study from the interview show that the expert informants have positive perceptions and attitudes towards the ECWMF. They unanimously agree that the Model is a viable alternative for sustainable higher education funding in Malaysia. Similarly, the findings from the quantitative survey data are also positive and promising. The study finds that: (1) when a higher education's students has a favourable attitude towards the ECWMF, he/she is more likely to be a participant; and, (2) if a higher education's students believes that he/she has a greater autonomy over factors that might impede or facilitate their participation, the stronger his/her intention to participate in the ECWMF.